Binary and Ternary Manganese Dioxide Composites Cathode for Aqueous Zinc‐ion Battery. Issue 44 (29th November 2018) - Zhao, Ling; Dong, Liubing; Liu, Wenbao; Xu, Chengjun
Abstract: MnO2 is a traditional cathode material for aqueous zinc‐ion battery (ZIB). However, its extensive use is limited by its poor conductivity and cycling performance. Design of binary or ternary MnO2 composites is a useful way to enhance the performance of MnO2 . At first, a series of binary MnO2 /carbon nanotube (CNT) composites with different CNT contents were synthesized by a facile co‐precipitation method. The effect of CNT content on the properties of binary composites was investigated. In addition, the ternary MnO2 /CNT/polyaniline (PANI) composites were prepared to investigate the effect of unitary, binary and ternary composites on the MnO2 . The results show that an appropriate content of CNT decreases the charge transfer resistance of the composite leading to a good electrochemical performance. The addition of PANI stabilizes the cycle performance of the composite at a cost of a slight decrease in the specific capacity. Abstract : In this paper we synthesized unitary, binary and ternary composites on the MnO2 and investigated the difference among them. Binary MnO2 /CNT composites own a better performance in aqueous ZIB compared to unitary and ternary composites. Binary MnO2 /CNT composites with an appropriate content of CNT has the best electrochemical performance (∼ 310 mAh g −1 at 0.031 A g −1 and 60% capacity retention after 100 cycles in 2 M ZnSO4 ). For ternary composites, the addition of PANI stabilizes the cycle performance of the composite in 2 M ZnSO4 + 0.5 M MnSO4 (no capacity attenuation after 300 cycles).